2019
DOI: 10.1073/pnas.1816946116
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathway of globo-series glycosphingolipids and β1,3-galactosyltransferase V (β3GalT5) in breast cancer

Abstract: The globo-series glycosphingolipids (GSLs) SSEA3, SSEA4, and Globo-H specifically expressed on cancer cells are found to correlate with tumor progression and metastasis, but the functional roles of these GSLs and the key enzyme β1,3-galactosyltransferase V (β3GalT5) that converts Gb4 to SSEA3 remain largely unclear. Here we show that the expression of β3GalT5 significantly correlates with tumor progression and poor survival in patients, and the globo-series GSLs in breast cancer cells form a complex in membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…The glycolipid molecules SSEA-3 and SSEA-4 are known as embryonic stem cell markers that are identified in stem cells and cancer cells. 56,57 An expression of SSEA-4 was reported on porcine cardiac valves. 34 Zulli et al 35,58 reported that diseased human and rabbit blood vessels expressed for SSEA-4, and both SSEA-3 and SSEA-4, respectively, although normal blood vessels were negative for both SSEA-3 and SSEA-4.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolipid molecules SSEA-3 and SSEA-4 are known as embryonic stem cell markers that are identified in stem cells and cancer cells. 56,57 An expression of SSEA-4 was reported on porcine cardiac valves. 34 Zulli et al 35,58 reported that diseased human and rabbit blood vessels expressed for SSEA-4, and both SSEA-3 and SSEA-4, respectively, although normal blood vessels were negative for both SSEA-3 and SSEA-4.…”
Section: Discussionmentioning
confidence: 99%
“…This results in upregulation of multidrug resistance gene 1 (MDR1) expression as well (Ghandadi et al, 2019). Cerebrosides levels rise in numerous cancer cell lines, as an effect of glucosyl-and galactosyltransferase overexpression (Chuang et al, 2019;Zhu et al, 2005).…”
Section: Glycosphingolipidsmentioning
confidence: 99%
“…Carbohydrate structures have been suggested to be associated with poor prognosis and reduced overall survival in breast cancer [18]. Globo H is one of the GalNAc‐containing glycans bound by the rBC2LCN; it was first identified in MCF‐7 cells and was found to play crucial roles in cancer stem cell properties and tumor progression in breast cancer [8–9,19–21]. Globo H expression is higher in MCF‐7 and T‐47D cells than in MDA‐MB‐231 [13,19].…”
Section: Discussionmentioning
confidence: 99%